National Culture as a Moderator in Organizational Research - Mate DAMIĆ; Dora NALETINA; Luka BUNTIĆ (Communications of International Proceedings, 2020)
National culture is a master variable that defines ways in which societies function and differ one from another. Organizations competing on the global market need to take national culture into account when organizing their daily operations. There exists a significant body of literature that deals with different ways in which national culture affects organizations. The aim of this paper is to analyze national culture as a moderator in organizational research. In order to systematize the most recent findings we analyzed relevant literature since 2010 with a special emphasis on methodological and theoretical implications of using national culture as a moderator. Our paper identifies key research areas and avenues for future research of the moderating role of national culture in organizational research and provides methodological and theoretical suggestions for scientists entering the field.
Keywords: National culture; moderator; organizational research.